PENGARUH PROGRAM LOYALITAS TERHADAP KEPUASAAN PELANGGAN - Tia Hardiyanti; Cludia Ipara Riswardini; Anggit Dyah Kusumastuti (Politeknik Bisnis Indonesia, 2024)
This research aims to gather sufficient information about the impact of loyalty programs on customer satisfaction. This research method is a literature review based on several previous studies to answer the effect of loyalty programs on customer satisfaction. The results of this study indicate that loyalty programs have a significant effect on customer satisfaction. This can be seen in the results of previous research articles which show that loyalty programs have an effect on loyalty.